2016
DOI: 10.1016/j.jnc.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

The vegetation recovery pattern and affecting factors after pipeline disturbance in northwest China

Abstract: a b s t r a c tPipeline construction has severe disturbance on local ecosystems, especially in arid and semi-arid regions. Vegetation recovery along the pipeline is crucial for ecosystem management and eco-environment restoration. In this study, three typical regions with different backgrounds and engineering characteristics in northwest China were selected to analyze vegetation recovery pattern after pipeline disturbance by using comparative analysis and RDA analysis. The results showed that vegetation condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
(40 reference statements)
1
4
0
1
Order By: Relevance
“…Thin loamy 10 224 18) 366 (414 (Hammermeister et al 2003;Ganjegunte et al 2009;Wick et al 2009;Gasch et al 2014;Xiao et al 2016). In addition, there was a lack of effect of time since road removal on soil pH, which is similar to observations by Viall et al (2014) and Gasch et al (2016), who found soil pH did not reflect undisturbed soil conditions even after 55 yr post reclamation.…”
Section: Ecological Sitesupporting
confidence: 82%
“…Thin loamy 10 224 18) 366 (414 (Hammermeister et al 2003;Ganjegunte et al 2009;Wick et al 2009;Gasch et al 2014;Xiao et al 2016). In addition, there was a lack of effect of time since road removal on soil pH, which is similar to observations by Viall et al (2014) and Gasch et al (2016), who found soil pH did not reflect undisturbed soil conditions even after 55 yr post reclamation.…”
Section: Ecological Sitesupporting
confidence: 82%
“…Underground pipelines provide a quick and efficient means of transporting oil and gas due to their greater volume capacity, and low energy costs relative to rail or highway transportation (Xiao et al 2016; Horn et al 2021). Despite environmental concerns, pipeline demand has increased relative to other methods of transportation (Naeth et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Northern Shaanxi Loess Plateau region is an important energy base in China and plays an important role in the regional economy and ecology (Chen et al, 2012), such as the West-East Gas Pipeline, China, which is expected to have 240,000 km of pipelines by 2025 (The State Council Information Office of the People's Republic of China 2017). Pipeline construction inevitability causes different degrees of disturbance to the already fragile ecosystem, such as vegetation removal and ditch excavation along the pipeline's routes (Xiao et al, 2016). At the same time, this region is a typical ecologically fragile area that has complex terrain with deep loess and a semiarid monsoon climate, and soil is prone to erosion (Sun et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The pipeline laying process causes vegetation and soil disturbance, especially on slopes; without vegetation protection, soil erosion will be intensive along the banded disturbance areas (Keesstra et al, 2016), and concentrated runoff can trigger gully erosion and even affect the safety of pipelines (Nyssen et al, 2002). Therefore, rapid vegetation restoration in pipeline construction disturbance areas is important to control soil erosion and protect pipeline safety (Frankl et al, 2021; Xiao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%